EARNINGS MANAGEMENT IN CROWDFUNDING COMPANIES - Harinath, Preethi (2016)
Crowdfunding is a relatively new concept, which found footing in 2011. there are many crowdfunding platforms through which new businesses and entrepreneurs seek alternative finance and this method of finance is fast growing. This leads to the speculation that they might indulge in earnings management to report higher earnings to attract new investors. This could lead to declining performance in the future for these crowdfunding companies,despite their opportunistic forecasts.Investors depend on the financial statements provided by these companies to make an investment decision. Therefore to enable investors to make proper decisions and to allocate capital properly,this is needed. This dissertation is aimed at finding whether crowdfunding companies indulge in earnings management and thence,witness a fall in operating performance.